Perancangan Antarmuka Pengguna Situs Web E-Health untuk Layanan Pemeriksaan Penyakit Kulit menggunakan Pendekatan User-Centered Design (UCD) - Muhammad Luthfi Dani Kamil; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Skin disease is one of the most common diseases in Indonesia. In general, skin disease is not fatal, so its presence is often ignored, and people affected do not take it seriously. The solution for implementing E-Health in skin health services is to make it easier for people with skin diseases to get health services directly from specialist doctors. The design of the User Interface on the E-health Website in this study will use a User-Centered Design (UCD) approach. In designing the User Interface of the E-Health Website, the frequent appearance of Modal becomes a form of applying the principles of UCD. Modal is a solution because it can maximize Usability, Performance and simplify (Simplify) navigation. The design test in this study using the Single Ease Question (SEQ) questionnaire method resulted in an average score of 6.57 by public health center officers and 6.40 by public health center doctors. The total average satisfaction value of the two users is 6.48, which shows that the UI design of the E-Health Situs Web is easy to use.